Desenvolvimento de técnica molecular para avaliação da carga viral do HGV/GBV-C em pacientes co-infectados pelo HIV-1 - Alves, Viviane Kelly [UNIFESP] (2008)
Introduction: The HGV/GBV-C infection is frequent in humans and could last for years without evident clinical symptoms. HGV/GBV-C is a member of the Flaviviridae family strongly associated with the hepatitis C virus and composed by a single positive RNA strain. Recent studies suggest that HGV/GBV-C infection in HIV seropositive patients is associated with a delayed progression to AIDS, lower HIV viral load and a higher CD4 T-cell count, however, some studies failed to demonstrate such beneficial effects in these patients. Objectives: The aim of this study was to standardize a real time PCR to estimate the prevalence and HGV/GBV-C viral load among the HIV seropositive patients, comparing HIV monoinfected and co-infected in terms of T CD4 cell count and HIV viral load. Methods: To achieve this purpose, the 5’UTR genomic region of HGV/GBV-C was selected. A molecular cloning was needed in order to obtain a recombinant plasmid and a high production of this plasmid through a bacterial cloning in DH10B strain. The recombinant plasmid was linearized and submitted to in vitro transcription to obtain and to quantify synthetic RNA to construct the absolute quantification curve of the real time PCR system. The patient samples were submitted to the assay and the results were compared to the standard curve in order to obtain the HGV/GBV-C viral load. Results: A serial dilution of the synthetic RNA in factor 10 produced a quantification curve with 9 orders of magnitude, varying from 102 to 1010 genome equivalent/ìL. To the assay, the inclination of the straight line was -3.56, the intercept was 45.56, the Pearson correlation coefficient was r2=0.99 and the efficiency of the reaction was of 90.9%. The reproducibility of the assay was evaluated based on a quadruplicate reaction of the quantification curve with a mean coefficient of variation of 1.2%. 102 patients were included in the study, mean age of 42±9 years and 57.8% of them were man. From the total cohort, 21% were positive to HGV/GBV-C RNA in the plasma, with a mean viral load of 300.455 copies/mL and 26.4% were positive to anti-E2 antibodies. There were no statistical significance in regard to the CD4 T-cell count and HIV viral load when comparing HIV monoinfected patients with that co-infected with HGV/GBV-C (p=0,297)and a weak negative correlation was observed between HIV and HGV/GBV-C viral loads (Spearman’s= -0,237). Conclusions: The standardization of the real time PCR could be done and is in agreement with other published studies. According to the literature data, there is a high prevalence of the HGV/GBV-C infection among HIV seropositive patients. The weak negative correlation between HIV and HGV/GBV-C viral load is in agreement with previous publications, suggesting a beneficial effect regarding to AIDS progression, however, other factors can be associated and future studies are needed to better understand this viral interaction.